(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
The present article explores the theoretical foundations of the study of speaking verbs within the framework of lexical semantics, pragmatics, and discourse analysis. Speaking verbs constitute an important lexical group that expresses various forms of verbal communication, including informing, questioning, commanding, and expressing emotional attitudes. The study examines the semantic characteristics, classification, and pragmatic functions of speaking verbs in English and Uzbek. Particular attention is devoted to the role of these verbs in representing communicative acts and conveying the speaker’s intention, evaluation, and interpersonal relationships. The research demonstrates that speaking verbs form a complex lexical system that reflects the diversity of speech acts in human communication. A comparative analysis of English and Uzbek examples reveals both universal and language-specific features in the structure and usage of speaking verbs. The results show that these verbs play a significant role in organizing discourse, expressing attitudes, and enriching stylistic variation in language.